Model Pengembangan Wakaf Pondok Pesantren di Kota Pekanbaru - Astuti, Daharmi; Bakhri, Boy Samsul (UIR Press, 2025)
This research is motivated by the increasing development and large potential of waqf in Indonesia, but it has not yet been implemented optimally. Waqf, as an Islamic philanthropy, has a very important role in Islamic history. Waqf is also useful as a source of funding for the construction of mosques, hospitals, public facilities, and schools. The aim of this research is to determine the waqf management development model in Islamic boarding schools that are managed with waqf funds. This research is useful as 1) a reference and point of reference for stakeholders and waqf nadzir in developing waqf fund management, especially in Islamic boarding schools; 2) to provide information and socialize the community regarding the waqf development model for Islamic boarding schools in Pekanbaru city; and 3) to become an academic text for the development of sharia economic studies in general and waqf in particular. This type of research is field research with qualitative methods and a non-interactive qualitative approach. The data collection technique for this research uses interview techniques, documentation, and literature. The output of this research will be published in an accredited national journal and submitted as proceedings.